Student Nurses' Perceptions of Mercy: A Qualitative Study. Issue 1 (January 2021) - Thiel, Linda M.; Razmus, Ivy; Nauta, Becky; Keep, Suzanne; Thomas, Roberta; Moran, Katherine
Abstract : ABSTRACT: Mercy is a valued nursing attribute. It often identifies faith-based educational institutions, clinics, and hospitals and has been a quality valued and taught by the Catholic Sisters of Mercy through nursing's history. This qualitative study explored the meaning of mercy as expressed by undergraduate nursing students attending a faith-based nursing school. This article presents the findings of a question posed to students: What does mercy mean to me? Nursing practice and education implications are also presented.